FINITE ELEMENT ANALYSIS OF STRESSES AND DEFORMATIONS IN COLD PRESSURE WELDING ASSEMBLY - Florin CIOFU (Fiabilitate şi Durabilitate)
The non-detachable joining of materials with different nature under cold pressure, which we will refer to as "welding," is a form of solid-state diffusion that is unique because it is performed at normal working temperatures. Other forms of solid-state welding are performed at high temperatures, but even though these temperatures are high, the material is not melted, only more ductile. Although cold pressure welding has many important applications, it also presents aspects that are still uncontrolled in its fundamentals. The paper presents research in this field, bringing some original theoretical and practical contributions to the understanding of the principle of cold pressure welding and laying the foundations for the development of new processes that address modern materials. The approach is based on the "Advanced Meshing Tools" and "Generative Structural Analysis" modules of the CATIA software, which allow the simulation of the mechanical behavior of assembled structures, both by analyzing individual elements and as assemblies with connections modeled by idealized elements implemented in these modules. The paper will thus analyze the correlation between stresses and material deformations in the mechanically affected zone (MAZ).